La guerra salvadoreña vista desde la literatura autoficcional: Dios tenía miedo, de Vanessa Núñez Handal - Grinberg Pla, Valeria (2016)
This article analizes the labors of memory in Vanessa Núñez Handal’s novel Dios tenía miedo. By looking into both the familial and the national past in El Salvador through an autofictional exploration of the ways in which her own family was involved in the war she herself experienced as a child, Vanessa Núñez Handal experiments with the explanatory potential of both the creative imagination and the use of symbolic language, in a process where writing seems to be as much a method as a goal in order to remember and, above all, understand the percepticide that took place during the war. The ambiguity of the autofictional pact rules over the novel, giving her the liberty to combine fictional, autobiographical, and testimonial techniques, with the aim of articulating her interpretation of the traumatic past.